Principles of chemical separations with environmental applications - Noble, Richard D. (Cambridge University Press, 2003)
This introduction to chemical separations technology presents the chemical and/or physical basis of different techniques and explains how to evaluate them for design and analysis. Chemical separations are of central importance in many areas of environmental science, whether it is cleaning up polluted water or soil, the treatment of discharge streams from chemical processes, or modification of a specific process to decrease its environmental impact. This textbook is suitable for undergraduate and graduate students taking courses on environmental separations or environmental engineering. Many worked examples and over 100 homework problems are key highlights.